New and rare lingulate brachiopods from lower part of the Klabava formation (arenig, lower ordovician) of Prague Basin, Bohemia - Mergl,M. (Journal of the Czech Geological Society, 1997)
New ungulate brachiopod genera Sedlecilingula (type species S. sulcata sp. n.) and Collarotretella (type species C. septata sp.n.) are defined. Poorly known species of the genera Lingulella, Palaeoglossa, Spondyglosella and Rowellella are described or discussed. Comments on brachiopod associations, their stratigraphical age and environmental significance are given.
Keywords: Brachiopoda; Lingulata; Ordovician; Arenig; Bohemia